ESENSI KEBERSIHAN: Studi Komparasi Penafsiran antara Wahbah Al-Zuhaili dan Quraish Shihab terhadap QS. Al-Muddatsir: 4 - Setio Budi; Ahmad Yusam Thobroni; Mohammad Toha (STAI Asy-Syukriyyah, 2022)
The awareness of hygiene issues for Islam is deep. The Prophet Muhammad's hadith emphasized that Islam was built on immaculacy. Hygiene is the foremost prerequisite in operating out all parts of life, concerning outer and inner levels. This report portrays the interpretation of QS. al-Muddatsir:4 regarding hygiene's topic utilizing a comparative interpretation approach between Wahbah al-Zuhaili and Quraish Shihab. This investigation desires to discover the hygiene substance amid numerous distinct interpretations. The research approach used is to perform a descriptive study of the collected library data. The outcomes demonstrated that the bits of knowledge between Wabah al-Zuhaili and Quraish Shibab were distinguishable. Al-Zuhaili interpreted